Electroacupuncture Therapy Effectively Protects the Rat Brain after Intracerebral Hemorrhage - Li Huang; Xuehui Fan; Yao Chen; Heng Lin; Xiaoqian Jiang; Chaoxian Yang (Neural Plasticity)
Objective. Electroacupuncture (Ea) is a useful complementary and alternative therapy for intracerebral hemorrhage (ICH). However, the neurobiological basis for the Ea treatment of ICH is still unclear. The primary aim of the present study was to explore whether Ea prevents brain edema, apoptosis, excitotoxicity, and neuroinflammation in rats after hemorrhagic stroke. Methods. Rats were randomly divided into Sham, Control, and Ea groups. We used modified neurological severity score (mNSS) and gait analysis to estimate neurological function in rats, and PET/CT to assess glucose uptake and the hemorrhagic focus volume. Measurement of the brain water content and TUNEL staining were used to evaluate brain edema and cell apoptosis, respectively. The serum myelin basic protein (MBP), neuron-specific enolase (NSE), calcium-binding protein B (S100B), and tumor necrosis factor-α (TNF-α) concentrations were examined with ELISA. The expression levels of the CD68, GALC, Arg-1, iNOS, NR2A, Glu2R, AQP4, MAP2, GFAP, AQP9, Bcl-2, Bax, and Glu proteins around the hematoma were detected via immunohistochemistry staining. Western blot was used to analyze the levels of the AQP4, AQP9, Bax, Bcl-2, iNOS, and Arg-1 proteins. Results. Ea treatment improved neurological function and reduced the hemorrhagic area and brain water content in rats after ICH. The serum concentrations of MBP, NSE, S100B, and TNF-α all decreased significantly in the Ea group compared with the Control group. Expression levels of the Glu, NR2A, AQP4, AQP9, Bax, GFAP, iNOS, and CD68 proteins in brain tissue surrounding the hematoma were obviously suppressed in ICH rats following Ea treatment. Moreover, Ea stimulation increased the levels of the MAP2, GALC, Glu2R, Arg-1, and Bcl-2 proteins, but reduced the number of TUNEL-positive cells in rats after ICH. Conclusion. The results of this study suggest that Ea may exert neuroprotective effects by suppressing brain edema, apoptosis, excitotoxicity, and neuroinflammation.